Development of flame-retarding elastomeric composites with high mechanical performance. (June 2018) - Araby, Sherif; Wang, Chun-Hui; Wu, Hao; Meng, Qingshi; Kuan, Hsu-Chiang; Kim, Nam Kyeun; Mouritz, Adrian; Ma, Jun
Abstract: Flammability of polymers is a major issue limiting their applications where fire safety is paramount, and a great challenge is to make polymers flame-retarding with no sacrifice of their mechanical performance. This work employed a low-cost graphite intercalation compound (GIC) as a multifunctional additive to improve the flame retardancy and mechanical strength of an elastomer by melt compounding. As characterized by cone calorimetry which presents real fire conditions, the average peak heat release rate and mass loss rate were reduced by 55% and 54% and the fire performance index enhanced by 60% at 12.0 vol% GIC, which implies a lot more time for fire victims to escape and to be saved. It inhibited the elastomer flammability through two consequential processes: (i) endothermic chemical reactions during the GIC expansion and (ii) char layer formation on composite surface protecting the polymer beneath from burning. Tensile strength, Young's modulus, elongation at break and tear strength were respectively improved by 230%, 100%, 220% and 200%. These findings demonstrate that GICs can provide both flame retardancy and reinforcement to elastomers which are extensively used in industries.